Discourses and Social Praxis of Entrepreneurship. A Glance from the Critical Discourse Analysis (2019)
The objective of this article is to socialize some findings related to the understanding of the discourses that guide the teaching of entrepreneurship in Higher Education Institutions in Medellin city. It is explored through a qualitative approach and the Critical Discourse Analysis Methodology, its "construction" through the discursive practices with people in charge of the social praxis of the analyzed institutions. It identifies commonalities and differentiators that support the "discourse" (values, ideologies and discursive devices used in each). The information was gathered through semi structured interviews and textual analysis of the structure of institutional newspaper news. It also provided an institutional context in which students understand, memorize and use the entrepreneurship information for their social praxis. In the given discourse, the use of semantic macrostructures is evident, providing cohesion and coherence in each of the analyzed institutions.